Temporal sequence of recovery-related events following maximal exercise assessed by heart rate variability and blood lactate concentration - Hoshi, Rosangela Akemi; Vanderlei, Luiz Carlos Marques [UNESP]; de Godoy, Moacir Fernandes; Bastos, Fábio do Nascimento; Netto, Jayme [UNESP]; Pastre, Carlos Marcelo [UNESP] (Wiley, 2017)
Purpose: To analyse the temporal sequence of recovery events related to autonomic nervous system and metabolic processes following maximal exercise, applying linear and nonlinear indices of heart rate variability (HRV) and blood lactate concentration. Methods: On the following day of the maximum oxygen consumption test, 20 participants firstly lay down for 20 min for resting data collection and then underwent the constant velocity exhaustive test, which consisted in running at 100% of maximal velocity reached on the previous day until exhaustion. Immediately after the end of exercise, the participants kept a supine position for 120 min recovering passively. Prior to exercise and at every 10 min during the recovery time, blood samples were collected to determine lactate concentration, and heart rate variability analysis (time and frequency domain indices and recurrence plot variables) was performed. Friedman's test, complemented with Dunn's multiple comparison test, was used to compare recovery moments and baseline values. Results: From 70 min, no significant differences were detected between lactate concentration and baseline. HRV indices were considered recovered at different timings: at 60 min for SD2; at 70 min for SDNN and LF; at 80 min for RMSSD, HF and SD1 and at 90 min for recurrence plot variables. Conclusions: During passive recovery after maximal exercise, restoration processes seem to comply an order, considering analysed HRV indices and lactate removal: at first, lactate concentration reaches normal values, allowing sympathovagal reorganization, and then, parasympathetic function is able to complete its reestablishment followed by system complexity recovering.
Keywords: autonomic complexity; autonomic nervous system; linear indices; physiological recovery; recurrence plot